Radiocarbon age and chronology of sediment core SK-312/12 - Sanjit Kumar Jena; Ravi Bhushan; Partha S Jena; Nisha Bharti; A K Sudheer; Prasanta Sanyal; Ajay Shivam; Ankur Dhabi (PANGAEA, 2025)
Sediment core SK-312/12 was collected from the Equatorial Indian Ocean at 3750m b.s.l.. Radiocarbon age-depth profile was continuous up to 70 cm of the core length. The core was sampled at each 1 cm interval. Nearly alternate sections were processed to separate foraminiferal carbonates from the bulk sediment. Radiocarbon ages were obtained from radiocarbon dating of mixed-layer species Globigerinoides ruber and Trilobatus sacculifer taken in sub-equal amounts from 250-425μm size fraction. The radiocarbon ages were calibrated with respect to the MARINE20 Calibration curve (Heaton et al., 2020) with a modern reservoir age (ΔR) of -54 + 65 yr (Dutta et al., 2001; Southon et al., 2002) under the R package "Bacon" (Blaauw & Christeny, 2011), and the Bayesian chronology was obtained.
In: Jena, SK et al. (2025): Radiocarbon age and chronology of sediment core SK-312/12, along with Magnesium/Calcium and δ^1?O measurements on Trilobatus sacculifer (w/s), and paleotemperature and paleosalinity records [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974306